2006
DOI: 10.1021/ol053094w
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Carbonate-Promoted Stereospecific 5-Endo-Trig Cyclization of Unactivated Allenes in the Absence of Any Transition Metals

Abstract: Formation of 3-pyrrolines from simple unactivated allenes bearing a protected amino group under basic conditions is described. Treatment of alpha-amino allenes with potassium carbonate in DMF under reflux in the absence of any transition-metal catalysts gave the corresponding 3-pyrrolines in good to excellent yields, by 5-endo-trig mode cycloisomerization. The reaction of internal allenes with an axial chirality afforded the corresponding 3-pyrrolines in a stereoselective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 62 publications
0
21
0
1
Order By: Relevance
“…While the use of free amino groups lead to reaction times of several days, with sulfonamides as well as acetyl or Boc protecting groups result in a fast conversion (but with the latter two the diastereoselectivity was low) 314. Ohno, Tanaka, et al have recently shown that the sulfonamides readily cyclize with potassium carbonate in DMF in the absence of any transition‐metal catalyst 315. Lee et al have applied the gold‐catalyzed methodology to the synthesis of bicyclic β‐lactams 316.…”
Section: Nucleophilic Additions To π Systemsmentioning
confidence: 99%
“…While the use of free amino groups lead to reaction times of several days, with sulfonamides as well as acetyl or Boc protecting groups result in a fast conversion (but with the latter two the diastereoselectivity was low) 314. Ohno, Tanaka, et al have recently shown that the sulfonamides readily cyclize with potassium carbonate in DMF in the absence of any transition‐metal catalyst 315. Lee et al have applied the gold‐catalyzed methodology to the synthesis of bicyclic β‐lactams 316.…”
Section: Nucleophilic Additions To π Systemsmentioning
confidence: 99%
“…Während freie Aminogruppen zu einer Reaktionszeit von einigen Tagen führen, ist mit Sulfonamiden sowie der Acetyl‐ oder tert ‐Butoxycarbonyl(Boc)‐Schutzgruppe eine schnelle Umsetzung möglich (mit den beiden zuletzt genannten ist die Diastereoselektivität jedoch niedrig) 314. Ohno, Tanaka et al haben kürzlich gezeigt, dass Sulfonamide auch in Abwesenheit jeglichen Übergangsmetalls mit Kaliumcarbonat in DMF cyclisieren 315. Lee et al haben diese Gold‐katalysierte Methode zur Synthese bicyclischer β‐Lactame genutzt 316.…”
Section: Nucleophile Additionen An π‐Systemeunclassified
“…Malonate‐tethered allenyl substrates 1 , 3 , 5 , 7 , 9 , and 13 were prepared from dimethyl 2‐(buta‐2,3‐dien‐1‐yl)malonate10 and benzyl bromide derivatives according to the general procedure. N ‐Ts‐tethered allenyl substrate 11 was prepared from N ‐(buta‐2,3‐dien‐1‐yl)‐4‐methylbenzenesulfonamide11 and p‐tert ‐butyldimethylsilyloxybenzyl bromide according to the general procedure.…”
Section: Methodsmentioning
confidence: 99%